On the Relationship between Intangible Cultural Heritage and the Collection of Superstitions at the Slovene Ethnographic Museum - Pukl, Adela (Traditiones, 2013)
<span style="line-height: 115%; font-family: ’Helvetica’,’sans-serif’; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">V članku je predstavljen nastanek zbirke vraževerja v Slovenskem etnografskem muzeju, zbiranje in dokumentiranje predmetov vraževerja ter pomembnost ohranjanja, dokumentiranja in raziskovanja nesnovne kulturne dediščine za celovito obravnavo vraževerja. <span style="line-height: 115%; font-family: ’Helvetica’,’sans-serif’; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">*** <span style="line-height: 115%; font-family: ’Helvetica’,’sans-serif’; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">This paper presents the establishment of a collection of superstitions in the Slovene ethnographic museum, describes collection and documentation of objects of superstition and addresses the importance of conservation, documentation and research of intangible cultural heritage for a comprehensive treatment of superstition.